The heart of Revelation : understanding the 10 essential themes of the Bible's final book - Duvall, J. Scott (Baker Books, 2019)
"Let anyone who has ears to hear listen to what the Spirit says to the churches." The book of Revelation speaks powerfully to every aspect of the Christian life, and the modern church desperately needs the vision of hope that it provides. In this thematic approach to the Bible's final book, author J. Scott Duvall identifies ten major themes, including: God and his people, worship, enemies, the mission, and the new creation. In The Heart of Revelation, readers will understand how to read Revelation in context, asking, "What are the main truths and realities of Revelation that we can know for certain?" and learning how these truths are relevant to our lives as modern-day believers